Regret Bias – Aversion in Latecomers - Chyad, Alaa Abd Ali; Sabab, Azhar Mohammed Majeed (Journal of Posthumanism, 2025)
Studies indicate that cognitive biases, especially regret-aversion bias, which represents "making a decision to avoid making the same mistake for fear of facing the same loss," cause negative reactions from peers, especially new students. This phenomenon often leads to academically backward students withdrawing socially from the school environment. The study aimed to identify regret-aversion bias among academically backward students in high school, and the significance of differences in regret avoidance according to the variable of gender (males/females) and specialization (scientific/literary).